Research on Computer Network Virus Defense Technology in Cloud Technology Environment - Singha, Anjani Kumar (IJRDO -Journal of Computer Science Engineering, 2017)
With the rapid development of the Internet, the antivirus software of the network is alwaysemerging and constantly changing. Traditional detection methods can’t effectively kill the newviruses and malicious software, the complexity of which also makes itself easy to be attacked bymalicious software. The emergence of cloud computing has changed the status quo. Therefore, thearchitecture model of virus malware detection based on cloud computing is proposed in this paper.Based on the combination of the method for detecting malicious software virus based on cloudcomputing and the algorithm analysis theory in machine learning, a new type of distributed CFOalgorithm is proposed, and the closed environment of cloud computing virtual machine nodes is usedto realize dynamic behavior monitoring to the virus malware, then the distributed fluctuations PIFalgorithm is used to describe the process of dynamic analysis and analysis reporting, besides, thewave algorithm is carried out corresponding improvement based on the analysis of the environment.Experimental results show that the model can detect the conditional trigger behavior of virusmalware, so as to find the conditions for triggering malicious behavior and the input data that satisfythese conditions and the performance of this monitoring system is greatly improved compared withthe common single machine system